Dampak Media Sosial Terhadap Keputusan Pembelian Konsumen di E-Commerce - M. Raghil; Hendra Riofita (STIKes Ibnu Sina Ajibarang, 2024)
This study examines the impact of social media on consumer purchasing decisions in e-commerce. With advancements in information technology, social media platforms such as Instagram, TikTok, and Facebook have evolved from mere promotional tools into essential means of building brand awareness and consumer trust. Social media facilitates direct interactions with consumers through visual content, customer reviews, and influencer collaborations, creating more personal and emotional shopping experiences. Additionally, features like TikTok Shop streamline promotion and purchasing processes on a single platform, offering new business opportunities. The study also highlights the role of testimonials, reviews, and influencer marketing in shaping purchasing decisions. Findings indicate that social media enhances brand awareness, fosters trust, and drives consumer loyalty, ultimately strengthening brand image in the digital marketplace.